Bioprospecting of Edible Fruit and Ethnomedicinal Trees: Pathways for Conservation in the UNESCO Biosphere of Apayao, Philippines - Martin, Hannie T. (Research in Ecology, 2025)
This study was undertaken in the upper and lower municipalities of Apayao Province, namely Luna, Pudtol, Kabugao, and Calanasan, integrated in the Northern Luzon forest ecosystems. It sought to characterize the external physical traits and perform in vitro analysis of selected five (5) edible fruit and ethnomedicinal trees, focusing on their ecological status, chemical composition, and conservation significance. Specifically, the research aimed to determine the phytochemical composition and cytotoxicity patterns of these species, to identify the environmental threats compromising their survival, and to propose policy recommendations in support of biodiversity conservation and sustainable forest governance. Fieldwork, tree species identification, habitat characterization, and preparation of specimens for laboratory analyses were done. Key Informant Interviews were employed to incorporate community-based ecological knowledge in relation to observed threats. The approach is through open-ended questions, flexible discussion, and follow-up probing. Morphological characterization and phytochemical screening revealed the presence of secondary metabolites such as tannins, flavonoids, and saponins, while cytotoxicity assays demonstrated moderate to high inhibition of breast cancer cell proliferation. These findings underscore the possibility of health advantages of the province’s forest natural resources. Results further revealed that the ecological status of the studied trees ranges from vulnerable and threatened to least concern, showing different levels of conservation priority. Major threats documented included extreme weather events (typhoons, droughts), the occurrence of pests and diseases, and manmade induced pressures such as forest clearing. Policy recommendations were crafted to support local ordinances that strengthen conservation and protection measures.